“E-commerce: Business & Legal Ethics” - ., Chitrangda (International Journal of Scientific Research and Management (IJSRM), 2014)
E-commerce presents a world of opportunity for doing businesses, reaching global markets and purchasing without leaving the home or office. E-commerce can provide opportunities to improve business processes, just as phones, faxes and mobile communications have in the past. However, just as any new business tool has associated issues and risks, e-commerce does have some issues too. It’s important to understand the ethical and legal issues concerning e-commerce to ensure a safe and secure environment for trading with customers and other businesses. Therefore to ensure the longer-term success of e-Business there have been calls for an adequate enabling framework to be put in place, particularly of a legislative nature. Stakeholders are demanding a more stable environment in which to conduct routine business and consumer transactions. Business ethics is a system of moral principles applied in the commercial world. It is a whole new scientific area because it combines law theory and politics as much as philosophical and historical documents. Ethics become a term very flexible and have many different aspects. Business ethics provide guidelines for acceptable behavior by organizations in both their strategy formulation and day-to-day operations. An ethical approach is becoming necessary both for corporate success and a positive corporate image. Especially nowadays ethics in business are obligated because many businessmen are only interested in making money despite the ethical costs or the harm they would probably cause to people or even to nature (environmental pollution).